2021
DOI: 10.1002/pmrj.12524
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Physical Medicine and Rehabilitation Match: Analysis of NRMP Data from 2007 to 2018

Abstract: Introduction We provide an updated analysis of data about U.S. Physical Medicine and Rehabilitation (PM&R) residency program applicants collected by the National Resident Matching Program (NRMP). Objective Analyze trends within NRMP data for PM&R residency match rates, compare matched to unmatched applicants, and compare PM&R applicants to other medical specialties. Design Secondary analysis of NRMP data. Setting NRMP data set. Participants Residency program applicants who participated in the NRMP Match, 2007 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…We were very interested to read the article titled "Trends in the Physical Medicine and Rehabilitation Match: Analysis of NRMP Data from 2007 to 2018" by Claus et al and appreciate their updated analysis of the data regarding U.S. physical medicine and rehabilitation (PM&R) residency program applicants. 1 This article validates that securing a PM&R residency has become more competitive and provides useful comparisons between matched and unmatched applicants. We applaud the authors for emphasizing longitudinal data specific to PM&R and highlighting factors correlated with a successful match into a PM&R residency program, which include length of rank order list andamong U.S. allopathic senior applicants-the number of volunteer experiences and publications.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…We were very interested to read the article titled "Trends in the Physical Medicine and Rehabilitation Match: Analysis of NRMP Data from 2007 to 2018" by Claus et al and appreciate their updated analysis of the data regarding U.S. physical medicine and rehabilitation (PM&R) residency program applicants. 1 This article validates that securing a PM&R residency has become more competitive and provides useful comparisons between matched and unmatched applicants. We applaud the authors for emphasizing longitudinal data specific to PM&R and highlighting factors correlated with a successful match into a PM&R residency program, which include length of rank order list andamong U.S. allopathic senior applicants-the number of volunteer experiences and publications.…”
supporting
confidence: 53%
“…In addition, IMG applicants may add to the diversity of PM&R though their high number of work experiences, as demonstrated in Table 3 of this article. 1 A lack of diversity in program leadership may contribute to unconscious bias, which may further exacerbate the lack of interview invitations and residency program selection of U.S. and non-U.S. IMG applicants. Programs should be encouraged to conduct internal reviews of their recruitment process to identify unconscious biases, provide training on unconscious bias to all staff involved, and focus on holistic recruitment strategies such as adversity indices and targeting applicants who are routinely excluded by traditional screening tools.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to receiving fewer interviews than matched applicants, limiting the pool of programs they were capable of ranking. A study by Claus et al 11 showed unmatched applicants tended to have lower United States Medical Licensing Examination (USMLE) Step 1 and Step 2 scores along with other traditional measures of competitiveness than matched applicants, supporting this notion. A study by Liang et al 12 also found that unmatched applicants submitted significantly more applications to achieve the same number of interviews as matched applicants, further supporting this explanation.…”
Section: Discussionmentioning
confidence: 96%
“…These findings of increased congestion in the NRMP are comparable to results from a previous study by Claus et al which analyzed trends in the Physical Medicine and Rehabilitation match and found an increase in the number of applicants in addition to increased rank order list length for matched applicants across 11 match cycles. 5 However, this study did not examine trends across multiple specialties, thus limiting any conclusions regarding the NRMP as a whole.…”
Section: Discussionmentioning
confidence: 99%